Beam squint effect in multi-beam mmWave massive MIMO systems - Afeef, Liza; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers Inc., 2022)
In multicarrier wideband millimeter-wave (mmWave) communications, as the size of antenna array increases, as in massive multiple-input multiple-output (MIMO), an additional propagation delay of the electromagnetic wave at each antenna element is introduced comparable to (or greater than) the symbol duration, resulting in producing a displacement in beam direction at each subcarrier frequency or as it calls beam squinting. With multi-beam transmission in massive MIMO systems, due to beam squinting effect, an additional inter-beam interference (IBI) can be introduced to the system which significantly decreases the overall system capacity. Therefore, in this paper, IBI under beam squint effect is modeled for different subcarrier frequencies and beam angles in a multi-beam mmWave massive MIMO system. In addition, the impact of this IBI model on the system capacity is evaluated. The analysis results show that beam squinting causes a significant increase in IBI level, even when transmitting with orthogonal beams. Moreover, the results provide the optimal number of beams for a given antenna array size to maximize the system's capacity considering beam squinting phenomena.
Keywords: Beam Squint Effect; Capacity; Inter-Beam Interference (IBI); Massive MIMO; Mmwave; Orthogonal Beams